1991
DOI: 10.1523/jneurosci.11-09-02914.1991
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of delayed neuronal death in the hippocampus by nerve growth factor

Abstract: Selective neuronal death in the CA1 sector of the hippocampus [delayed neuronal death (DND)] develops several days after transient global cerebral ischemia in rodents. Because NGF plays a potential role in neuronal survival, it was decided to study its effect in DND. We report here that intraventricular injection of NGF either before or after 5 min forebrain ischemia in the Mongolian gerbil significantly reduced the occurrence of DND. The tissue content of NGF in the hippocampus was decreased 2 d after ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
1
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(74 citation statements)
references
References 53 publications
1
70
1
2
Order By: Relevance
“…In contrast to this finding, Buchan et aI. (1990), using a fivefold higher dose than ours in the four-vessel occlusion model and chronically pretreating the rats for 11 days before the insult, and Shigeno et al (1991), injecting gerbils with a bolus roughly six times the total dose we used, did see significant improvements in neurolog ical outcome. A recent publication has underscored the importance of using a sufficiently high NGF dosage for a pharmacological effect (Yamamoto et aI., 1992).…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast to this finding, Buchan et aI. (1990), using a fivefold higher dose than ours in the four-vessel occlusion model and chronically pretreating the rats for 11 days before the insult, and Shigeno et al (1991), injecting gerbils with a bolus roughly six times the total dose we used, did see significant improvements in neurolog ical outcome. A recent publication has underscored the importance of using a sufficiently high NGF dosage for a pharmacological effect (Yamamoto et aI., 1992).…”
Section: Discussioncontrasting
confidence: 86%
“…NGF protects neurons against hypoxic, hypoglycemic, and excitotoxic damage in vitro and ischemia in vivo (Cheng and Mattson, 1991;Shigeno et al, 1991;Mattson and Cheng, 1993;Mattson et al, 1993a,c). SH-SY5Y cells possess functional trkA receptors; NGF can differentiate SH-SY5Y cells (Baker et al, 1989;Poluha et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured injured rat auditory neurons, TGF-�l enhanced the expression of the fibroblast growth factor (FGF) receptor protein (Lefebvre et al, 1991). Both NGF and FGF have been shown to reduce excitotoxic damage in cul tured mammaliaI) cortical and hippocampal neurons (Mattson et al, 1989;Cheng and Mattson, 1992) and to protect CAl neurons from ischemic damage caused by transient forebrain ischemia in the Mon golian gerbil (Berlove et al, 1991;Shigeno et al, 1991). In addition, it has also been demonstrated that TGF-�l enhances its own expression in cul tured rat astrocytes (Lindholm et al, 1990).…”
Section: Discussionmentioning
confidence: 99%